2017
DOI: 10.1111/ajad.12620
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylcysteine in the treatment of craving in substance use disorders: Systematic review and meta‐analysis

Abstract: The safety profile of NAC and its favorable tolerability, in addition to being anover-the-counter medication, presents with an interesting potential clinical use for craving in SUDs. (Am J Addict 2017;26:660-666).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 36 publications
2
52
2
3
Order By: Relevance
“…Idiosyncratic adverse reactions, such as asthma and pulmonary hypertension, have been reported in animal, but not in human studies . In addition to the major mental disorders discussed so far, NAC has also shown to have efficacy in other mental disorders, such as substance use disorders and obsessive–compulsive disorder (OCD) . Furthermore, NAC is routinely used for treatment of Paracetamol poisoning .…”
Section: Discussionmentioning
confidence: 99%
“…Idiosyncratic adverse reactions, such as asthma and pulmonary hypertension, have been reported in animal, but not in human studies . In addition to the major mental disorders discussed so far, NAC has also shown to have efficacy in other mental disorders, such as substance use disorders and obsessive–compulsive disorder (OCD) . Furthermore, NAC is routinely used for treatment of Paracetamol poisoning .…”
Section: Discussionmentioning
confidence: 99%
“…N-Acetylcysteine (NAC), a precursor of L-cysteine and the antioxidant glutathione (GSH), is found in plants, especially the onion [96][97][98]. NAC has been used as an adjuvant therapy in many psychiatric disorders (e.g., Alzheimer´s disease, schizophrenia, autism, addiction, substance abuse, obsessive-compulsive and mood disorders [24,[99][100][101][102][103][104]), with promising results and no relevant side effects after its administration against inflammation [97]. The use of NAC in a chronic unpredictable mild-stress animal model inhibited the levels of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) in the hippocampus and prefrontal cortex and exhibited antidepressant-like effects [71].…”
Section: N-acetylcysteine Decreases Inflammatory Responsementioning
confidence: 99%
“…Several large blinded RCTs have produced promising results in the area of cannabis and cocaine abuse, with a reduction in craving and drug intake in the former instance and a reduction in craving in the latter case which seems to have been limited to addicts already in a state of abstinence (Gray et al, 2012;LaRowe et al, 2013;Roten et al, 2013). These and other studies were examined in a recent metaanalysis which concluded that larger trials involving the use of NAC as an adjunctive treatment of SUD should be considered given the promising, though inconsistent, results achieved thus far (Duailibi et al, 2017). The use of NAC in the treatment of methamphetamine addiction appears to be worthy of special focus as there is reasonable evidence that its use can reduce craving in individuals addicted to the substance (Mousavi et al, 2015).…”
Section: N-acetylcysteinementioning
confidence: 99%